1980
DOI: 10.1021/bi00547a034
|View full text |Cite
|
Sign up to set email alerts
|

Bilayers of phosphatidylserine: a deuterium and phosphorus nuclear magnetic resonance study

Abstract: The structure and motion of the phosphatidylserine molecule in bilayers have been studied with deuterium and phosphorus-3 1 nuclear magnetic resonance. The phase behavior and the thermodynamic properties of phosphatidylserine were further characterized by means of spin-label electron paramagnetic resonance and differential scanning calorimetry. 1.2-Dipalmitoyl-, 1,2-dimyristoyl-, and 1,2-dioleoyl-snglycero-3-phosphoserine were selectively deuterated in the fatty acyl chains, in the glycerol backbone, and in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
147
3

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 53 publications
29
147
3
Order By: Relevance
“…The presence of charged lipids such as DMPS [28], of ions [36] or of charged anaesthetics [37] near the deuterated head group of DMPC strongly modifies its conformation, as a result of the perturbation of the bilayer surface charge [43]. Partial neutralization or screening of DMPS charges by positive charges at the membrane surface allows the DMPC head group to recover its original conformation [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of charged lipids such as DMPS [28], of ions [36] or of charged anaesthetics [37] near the deuterated head group of DMPC strongly modifies its conformation, as a result of the perturbation of the bilayer surface charge [43]. Partial neutralization or screening of DMPS charges by positive charges at the membrane surface allows the DMPC head group to recover its original conformation [22].…”
Section: Discussionmentioning
confidence: 99%
“…The head group deuterated DMPC is a mixture of DMPC-& and DMPC-ds (9: 1, w/w). The spectrum from the protein-free dispersions ( fig.3a) shows three distinct quadrupolar splittings, the internal one (0.8 kHz) corresponding to the deuterons of the N(CD+ groups of DMPC-ds, the intermediate splitting (2.4 kHz) from the deuterons in &positions of DMPC-&, while the largest splittings partially resolved into two splittings (7.8 and 8.6 kHz) correspond to the two deuterons in cY-position of DMPC-& [28]. The magnitude of these splittings is unaffected by bound spectrin ( fig.3b) although the spectral lines are narrower in the presence of spectrin.…”
Section: 'H Nmr Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, −S CD can be calculated from H-NMR experiments of specific deuterated methylene groups along the hydrocarbon lipid tails with the axis normal to the lipid bilayer. 17,41,42 By simulation, the order parameters may be calculated from the methylene hydrogen orientation with respect the z-axis normal to …”
Section: A Surface Area and Deuterium Order Parametersmentioning
confidence: 99%
“…Each lipid has its specific transition temperature at which the acyl chains undergo dramatic conformational change [27]. So, in bilayers at neutral pH, DPPC, DPPS, and DPPE have shown a phasetransition temperature of, respectively, 41.4°C, 53°C, and 63°C while SOPC monounsaturated glycerophospholipids have shown a transition temperature of 5.6°C [28][29][30][31]. In addition, it has been demonstrated that PEG increases the phase-transition temperature of glycerophospholipids, possibly by changing the solvation property of water [32][33][34].…”
Section: Discussionmentioning
confidence: 99%